Alkylidene Meldrum's Acids as Platforms for the Vinylogous Synthesis of Dihydropyranones. (6th April 2021) - Wittmann, Stéphane; Martzel, Thomas; Pham Truong, Cong Thanh; Toffano, Martial; Oudeyer, Sylvain; Guillot, Régis; Bournaud, Chloée; Gandon, Vincent; Brière, Jean‐François; Vo‐Thanh, Giang
Abstract: Upon Brønsted base organocatalysis, ketone‐derived alkylidene Meldrum's acids proved to be competent vinylogous platforms able to undergo a formal (4+2) cycloaddition reaction with dihydro‐2, 3‐furandione, providing an unprecedented route to 3, 6‐dihydropyran‐2‐ones as spiro[4.5]decane derivatives with up to 98 % ee thanks to the commercially available Takemoto catalyst. Preliminary investigation showed that this reaction could be extended to other activated ketones, establishing these alkylidene Meldrum's acids as a novel C4‐synthon in the vinylogous series. Abstract : Disubstituted alkylidene Meldrum's acids proved to be novel C4‐synthons capable of undergoing a vinylogous formal (4+2) cycloaddition reaction with reactive ketones, providing an unprecedented route to chiral 3, 6‐dihydropyran‐2‐ones under Brønsted base organocatalytic conditions.